Cloud‐Based Collaborative Writing and the Common Core Standards. Issue 3 (November 2014) - Yim, Soobin; Warschauer, Mark; Zheng, Binbin; Lawrence, Joshua F.
Abstract The Common Core State Standards emphasize the integration of technology skills into English Language Arts (ELA) instruction, recognizing the demand for technology‐based literacy skills to be college‐ and career‐ ready. This study aims to examine how collaborative cloud‐based writing is used in in a Colorado school district, where one‐to‐one computer access with netbooks and open source software is provided to all students. Specifically, this paper highlights how the middle school students' online writing align with the specific domains of the Common Core ELA Standards. Implications for practices are also discussed based on the challenges and affordances of using cloud‐based collaborative writing in the district.